Implementation of thematic bureaucratic reform policy in the organization section of the regional secretariat of Sumedang regency - Sintia Dwia Putri; Cindy Marcelia; Rizky Ilhami (Jurnal Scientia, 2024)
This study examines the Implementation of Thematic Bureaucratic Reform Policy in the Organization Section of the Regional Secretariat of Sumedang Regency. Therefore, related to the thematic bureaucratic reform policy implemented by the organizational section of the Sumedang Regency Regional Secretariat, this study describes things that explain how the implementation of thematic bureaucratic reform policies in the organizational section of the Sumedang Regency Regional Secretariat. This study used a descriptive method with qualitative data. Data were obtained from interviews and documentation studies. Based on the results of the research, the author obtained the implementation of thematic bureaucratic reform policies in the organizational section of the Sumedang Regency Regional Secretariat, but there were still obstacles faced such as lack of human resources and funds, the absence of SOPs regarding the implementation of bureaucratic reform in writing. Thematic Bureaucratic Reform Policy is expected to have an impact on the future.